Validation of a rapid and sensitive LC-MS/ MS method for determination of exemestane and its metabolites, 17β-hydroxyexemestane and 17β-hydroxyexemestane-17-O-β-D-glucuronide: Application to human pharmacokinetics study - Wang Lingzhi (Public Library of Science, 2015)
10.1371/journal.pone.0118553